Thermal property of polypropylene (PP) / recycle polyethylene terephthalate (rPET) blends / Syukri Ahmad ... [et al.] - Ahmad, Syukri; Syahmi, Eizlan; Nizu, Aminah; Johari, Afiqah; Mustafa, Haikal (2018)
Plastics such as polyethylene terephthalate (commonly referred as PET) are currently having tremendous demand from consumer. However due to its properties, which take longer time to naturally degrade, it became one of the major contributor to the environmental waste problem. So, an investigation is conducted to study the thermal properties of polypropylene (commonly referred as PP) composites that contain recycled PET (rPET) as its filler. The PP/ rPET blend was made using of single screw- extruder machine and produced a hot long chain. Next, the long chain was cooled before its get shredded into pallet form by using a palletizer. Then, the product was tested using Differential Scanning Calorimetry (DSC) to analyze its thermal properties. The result shows that by blending PP composites with rPET makes the thermal properties of PP composite increase. Increasing the composition of rPET in a PP/ rPET blend had increase the melting point, Tm and the transition-glass temperature,